DY-10 (Decorative screen) technical data sheet (RFA-026_Rev A) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of technical data sheet of DY-10 (Decorative screen).